2010
DOI: 10.5551/jat.3848
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Aggressive Statin Improves Vascular Endothelial Function in Patients with Stable Coronary Artery Disease

Abstract: Aim:The clinical relevance of the suggested pleiotropic effects of hydroxymethylglutaryl coenzyme A reductase inhibitors (statins) is controversial. Aggressive statins effectively reduce lipid levels, but whether their other effects are more powerful than those of regular statins is unknown. Methods: We enrolled 32 patients (mean age, 65 y; male, 23) who had undergone coronary revascularization over 6 months previously and whose serum LDL cholesterol levels persisted at 100 mg/dL, regardless of pravastatin (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Increases in CD and TBARS levels in serum of venous and arterial blood of patients with CAD suggested increased production of lipid peroxidation. The results obtained for TBARS levels are consistent with recently published observations which showed increased TBARS levels in patients with CAD [29][30][31]. However, Halevy et al [32] found no change in TBARS levels of CAD patients.…”
Section: Discussionsupporting
confidence: 82%
“…Increases in CD and TBARS levels in serum of venous and arterial blood of patients with CAD suggested increased production of lipid peroxidation. The results obtained for TBARS levels are consistent with recently published observations which showed increased TBARS levels in patients with CAD [29][30][31]. However, Halevy et al [32] found no change in TBARS levels of CAD patients.…”
Section: Discussionsupporting
confidence: 82%
“…The majority of patients were on statin therapy (75%) at baseline, and had lower levels of sCD40L compared to those that were not. Statin use has been shown to significantly decrease sCD40L levels in patients with coronary artery disease (CAD) 40, 41 . Although aspirin has been shown to suppress sCD40L levels in patients with chronic heart failure 42 , we did not see an effect of aspirin use in the current cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Han ve arkadajlannm PD hastalannda yaptigi çalijmada valsartan tedavisine eklenen statinin sadece ARB tedavisine göre endotel fonksiyonlanni daha iyi korudugu gözlenmijtir (24). ileri dönük yapilan bir çalijmada stabil koroner arter hastaligi olanlarda agresif statin tedavisine geçen hastalarda endotel fonksiyonlarmí n daha iyi korundugu bulunmu §tur (25). Bajka bir çalijmada ise atorvastatinin tip 2 DM'lu hastalarda endotel fonksiyonlannda iyiiejme yaptigi saptanmijtir (26).…”
Section: Tartiçmaunclassified